In-stent chronic coronary occlusion. Efficiency of revascularization and recanalization technique - S.M. Furkalo (Кардіохірургія та інтервенційна кардіологія)
The formation of neointimal hyperplasia after stent implantation and the occurrence of in-stent chronic coronary occlusion is considered a gradual process with possible formation of stable angina pectoris. Materials and methods. Our registry included 131 patients with restenotic changes in a previously implanted stent, which amounted 3.75 % of the total number of interventions during corresponding period. Among these, 36 (1.02 %) patients had chronic coronary occlusion in a previously implanted stent. In most cases, a multivessel disease occurred, the time after stenting was more than 78 months, and the course of the disease was symptomatic in all patients. Most often (38.2 %), stent occlusion was recorded in the left anterior descending artery. Results. Our results indicate that in the presence of conical (typed) proximal and distal occlusion cups, the recanalization efficiency was the greatest (86.6 %), providing intraluminal guidewire advancement both with antegrade access and in the case of a retrograde approach for recanalization of chronic occlusions in the stent. The most commonly used technique was using wires with increasing «load» on the tip until an effect is obtained (AWE – antegrade wire escalation). Conclusions. In contemporary conditions, recanalization of the in-stent chronic coronary occlusion is characterized by significant success (85–90 %). It is necessary to use coronary guidewire with a significant load on the tip, microcatheters with increased penetrating ability, as well as specialized microcatheters. High efficiency was demonstrated by tapped guidewires with a composite structure. Repeated stenting requires optimization using intravascular imaging techniques.